Determinan Kepatuhan Wajib Pajak Pribadi dan Pengaruhnya terhadap Penerimaan Pajak Penghasilan di Kantor Pelayanan Pajak Pratama Kota Malang - Roziq, Mohammad; Syafriel, Muhammad (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2024)
This study aims to examine the determinants of personal taxpayer compliance and its effect on income tax revenue at the Malang City Primary Tax Service Office. Determinants used as predictors of personal taxpayer compliance are viewed from the perspective of taxpayers: taxpayer awareness, taxpayer knowledge, perceptions of equality and fairness, and compliance costs; tax service office perspective: account representatives, fiscal service quality, and tax socialization; and the perspective of tax regulators: tax regulations, tax audits and fines and tax sanctions. This study involved 200 personal taxpayers registered at the Malang City Primary Tax Service Office. Sampling was done by convenience sampling technique. Hypothesis testing was carried out using the Structural Equation Model - Partial Least Square (SEM-PLS) using SmartPLS 3.27 program. The results showed that taxpayer awareness has a positive and significant effect on personal taxpayer compliance. Taxpayer knowledge has a positive and significant effect on personal taxpayer compliance. Perceptions of equality and fairness have a positive and significant effect on personal taxpayer compliance. Obedience costs have a positive and significant effect on personal taxpayer compliance. Account representatives have a positive and significant effect on personal taxpayer compliance. The quality of fiscal services has a positive and significant effect on personal taxpayer compliance. Tax socialization has a positive and significant effect on personal taxpayer compliance. Tax regulations have a positive and significant effect on personal taxpayer compliance. Tax audits have a positive and significant effect on personal taxpayer compliance. Tax fines and sanctions have a positive and significant effect on personal taxpayer compliance. Finally, personal taxpayer compliance has a positive and significant effect on tax revenue at the Malang City Primary Tax Office.